Pyroptosis and Its Regulation in Diabetic Cardiomyopathy - Lu, Yafang; Lu, Yaqiong; Meng, Jun; Wang, Zuo (Frontiers in Physiology, 2022)
Diabetic cardiomyopathy (DCM) is a prevalent disease, characterized by contractile dysfunction and left ventricular hypertrophy. Patients with DCM have high morbidity and mortality worldwide. Recent studies have identified that pyroptosis, a kind of cell death, could be induced by hyperglycaemia involving in the formation of diabetic cardiomyopathy. This review summarizes the regulatory mechanisms of pyroptosis in diabetic cardiomyopathy, including NLRP3, lcnRNAs, miRNAs, circRNAs, AIM2 inflammasome and some drugs.